AB1277 AUTOANTIBODIES IN NLRP3-ASSOCIATED AUTOINFLAMMATORY DISEASE: A CASE REPORT AND LITERATURE REVIEW. (2nd June 2020) - Zhang, L.; Sun, Y.; Li, Y.; Yu, W.; Wang, Y.; Wu, D.; Zhang, W.; Shen, M.; Wang, R.
Abstract : Background: We present the first report of high-titer autoantibodies in NLRP3 -associated autoinflammatory disease( NLRP3 -AID).Because systemic autoinflammatory disease(SAID) is characterised by the lack of autoreactive T-cells or autoantibodies, we made a systemic review on the theme of autoantibody in SAID to clarify this phenomenon. Objectives: We present the first report of high-titer autoantibodies NLRP 3-AID, and discuss autoantibody in classical SAID. Methods: We collected the clinical data of the patient with NLRP3 -AID who had high-titer autoantibodies, and made a systemic review about autoantibody in SAID. Results: A 38-year-old Chinese Han patient was definitely diagnosed as NLRP3 -AID because of cold-triggered urticaria-like rash and fever, arthralgia, binaural sensorineural deafness, chronic meningitis, high inflammatory marker and de novo NLRP3 T348M variant. Figure 1 shows pedigree of the patient.Meanwhile, she had positive antinuclear antibody(ANA) with a nucleolar pattern of 1:160, positive anti-β2GPI antibody 54-68 AU/ml (normal range < 20 AU/ml) and positive lupus anticoagulant 1.24-1.29 (normal range ≤ 1.2). Literature review found that 13 articles reported autoantibodies in Familial Mediterranean fever (FMF), and there was no autoantibody reported in hyperimmunoglobulinemia D syndrome (HIDS), TNF receptor–associated periodic syndrome(TRAPS) and NLRP3 -AID. The prevalence of ANA, anti-dsDNA, RF and anti-CCP in patients with FMF was similar to healthy controls. Conclusion: Patients with NLRP3 -AID can have high-titer ANA and APLs by accident. If patients with high-titer autoantibodies have characteristic manifestations of SAIDs instead of typical features of autoimmune diseases, we should make the final diagnosis through detailed investigation and genetic testing. References: [1]Ben-Chetrit E, Gattorno M, Gul A, et al. Consensus proposal for taxonomy and definition of the autoinflammatory diseases (AIDs): a Delphi study. Annals of the rheumatic diseases 2018; 77(11): 1558-65. [2]Kuemmerle-Deschner JB, Ozen S, Tyrrell PN, et al. Diagnostic criteria for cryopyrin-associated periodic syndrome (CAPS). Annals of the rheumatic diseases 2017; 76(6): 942-7. Disclosure of Interests: None declared